CLUSTER DEVELOPMENT AND INNOVATIVE POTENTIAL IN SERBIAN AGRICULTURE - Parausić, Vesna; Domazet, Ivana (Economics of Agriculture, 2018)
Science, technological development, innovation, competitive research for innovation, university-industry collaboration in R&D, quality of scientific research institutions and state of cluster development today are key factors of competitiveness and sustainable development of all economies. In this paper authors analyse the correlation of the state of cluster development and innovation in national economies and give recommendations and ways of improving the innovative potential in Serbian economy, with emphasis on agriculture sector. Research hypothesis is set as: expressed positive linear correlation exists between cluster development and national innovation potential, meaning that the countries in which clusters are deep and well-developed are at the same time countries which have a high national innovation potential and vice-versa. The source of the data analysed in this paper is the Competitiveness report of the World Economic Forum 2017-2018. Linear correlation, including confidence intervals, was used in data analysis and research hypothesis is accepted by the data. Application of innovations in production value chain requires stimulating innovation policy of the state, great financial investments in the private sectors, as well as professional support of scientific–research and educational institutions, through the cluster initiatives.